2017
DOI: 10.1186/s40478-017-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus tropism and interactions in myelinating neural cell cultures: CNS cells and myelin are preferentially affected

Abstract: The recent global outbreak of Zika virus (ZIKV) infection has been linked to severe neurological disorders affecting the peripheral and central nervous systems (PNS and CNS, respectively). The pathobiology underlying these diverse clinical phenotypes are the subject of intense research; however, even the principal neural cell types vulnerable to productive Zika infection remain poorly characterised. Here we used CNS and PNS myelinating cultures from wild type and Ifnar1 knockout mice to examine neuronal and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 99 publications
7
72
1
Order By: Relevance
“…ZIKV infection and replication has previously been shown for neuroglia within the CNS radial glia [34], myelinating oligodendrocytes [35] and astrocytes [36], but never for OECs, the neuroglia of the primary olfactory nervous system. OECs surround and support the axons of olfactory sensory neurons as they extend from the olfactory mucosa into the olfactory bulb in the brain, forming the olfactory nerve.…”
Section: Discussionmentioning
confidence: 95%
“…ZIKV infection and replication has previously been shown for neuroglia within the CNS radial glia [34], myelinating oligodendrocytes [35] and astrocytes [36], but never for OECs, the neuroglia of the primary olfactory nervous system. OECs surround and support the axons of olfactory sensory neurons as they extend from the olfactory mucosa into the olfactory bulb in the brain, forming the olfactory nerve.…”
Section: Discussionmentioning
confidence: 95%
“…Rather, myelin changes probably represent a combination of the arrest of myelination and the degradation of previously established sheaths. 185 Following reports linking ZIKV infection to GBS, it has been analyzed the peptide sharing between the virus and human proteins potentially related to GBS related proteins. 186 The immunological potential of the peptide sharing was described, which appeared to favor an autoimmune cross-reactive connection between ZIKV and GBS.…”
Section: Chikungunya Virus and Gbsmentioning
confidence: 99%
“…Based on these associations, a key question was whether the PNS was a direct target of infection or if the pathology was indirectly due to inflammatory responses, as was suggested by case reports of sensory neuropathy that developed weeks after the initial infection (Martinez et al 2017). In CNS and PNS myelinating cultures from Ifnar1 KO mice, all CNS cells were vulnerable to ZIKV infection, especially oligodendrocytes, but infection rates of PNS cells were much lower (Cumberworth et al 2017). A study using both hiPSCs and mouse models showed that ZIKV could directly infect PNS cell populations, especially neurons in vivo and in vitro (Oh et al 2017).…”
Section: Deficits In the Mature Nervous Systemmentioning
confidence: 99%